Perbedaan Kualitas Tidur antara Mahasiswa yang Mengalami dan yang Tidak Mengalami Computer Vision Syndrome (CVS) - Salman Faridy Febryan; Ike Rahmawaty Alie; Ariko Rahmat Putra (UNISBA Press, 2023)
Abstract. The government is trying to switch learning methods to online as to prevent the spread of COVID-19. Computer Vision Syndrome (CVS), also known as Digital Eye Strain (DES) emits a blue light spectrum that indirectly disrupts circadian rhythms, disrupting sleep quality. This study aims to analyze differences in sleep quality between students of the Faculty of Medicine at the Islamic University of Bandung class of 2019 who experienced and did not experience Computer Vision Syndrome (CVS) during the COVID-19 pandemic period. This study is an observational analytic study with a cross-sectional design using a comparative study approach. The sample for this research was 95 people using a random sampling technique in Unisba Faculty of Medicine students class of 2019 from June–December 2022. The data for the study were obtained by filling out the Computer Vision Syndrome Questionnaire (CVS-Q) and the Pittsburgh Sleep Quality Index (PSQI) questionnaires. Data analysis used the chi-square test to compare the two categorical groups. The results of this study showed that 82% of subjects did not experience CVS, while those who experienced CVS were 18%, and the percentage of poor sleep quality was 64%, while 36% had good sleep quality. The statistical test results obtained a value of p = 0.005 which showed that there was a significant difference in sleep quality between those who experienced and those who did not experience Computer Vision Syndrome (CVS in students of the Faculty of Medicine, Bandung Islamic University Class of 2019). Abstrak. Pemerintah mengupayakan peralihan metode pembelajaran menjadi daring sebagai pencegahan penyebaran COVID-19. Computer Vision Syndrome (CVS), dikenal juga sebagai Digital Eye Strain (DES) memancarkan blue light spectrum secara tidak langsung mengganggu irama sirkadian yang berakibat gangguan pada kualitas tidur. Penelitian ini bertujuan untuk menganalisis perbedaan kualitas tidur antara mahasiswa Fakultas Kedokteran Universitas Islam Bandung Angkatan 2019 yang mengalami dan yang tidak mengalami Computer Vision Syndrome (CVS) selama masa pandemi COVID-19. Penelitian ini adalah analitik observasional dengan desain cross-sectional menggunakan pendekatan komparatif studi. Sampel penelitian ini adalah 95 orang dengan teknik random sampling pada mahasiswa FK Unisba angkatan 2019 selama bulan Juni–Desember 2022. Data penelitian ini diperoleh dengan pengisian kuesioner Computer Vision Syndrome Questionnaire (CVS-Q) dan Pittsburgh Sleep Quality Index (PSQI). Analisis data menggunakan uji chi-square untuk membandingkan kedua kelompok kategorik. Hasil penelitian ini menunjukkan subjek yang tidak mengalami CVS sebanyak 82% sedangkan yang mengalami CVS sebanyak 18% dan persentase kualitas tidur buruk sebanyak 64% sedangkan kualitas tidur baik sebanyak 36%. Hasil uji statistika didapatkan nilai p=0,005 yang menunjukkan terdapat perbedaan bermakna kualitas tidur antara yang mengalami dan yang tidak mengalami Computer Vision Syndrome (CVS pada mahasiswa Fakultas Kedokteran Universitas Islam Bandung Angkatan 2019).